1984
DOI: 10.1115/1.3246710
|View full text |Cite
|
Sign up to set email alerts
|

Film Condensation of Refrigerant-113 and Ethanediol on a Horizontal Tube—Effect of Vapor Velocity

Abstract: Heat transfer measurements are reported for condensation of refrigerant-113 and ethanediol (ethylene glycol) on a single horizontal tube with vertical downflow. For refrigerant-113, vapor velocities up to around 6 m/s were obtained, while for ethanediol, velocities in excess of 100 m/s were obtained at low pressure. The results are compared with those of earlier investigators and with theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Here, the non-isothermality function is adopted from the experiment of Lee et al [21] for circular tube. Note that 0 6 A 6 1 and the amplitude A largely depends on the ratio of the outside-to-inside heat-transfer coefficients.…”
Section: Thermal Analysismentioning
confidence: 99%
“…Here, the non-isothermality function is adopted from the experiment of Lee et al [21] for circular tube. Note that 0 6 A 6 1 and the amplitude A largely depends on the ratio of the outside-to-inside heat-transfer coefficients.…”
Section: Thermal Analysismentioning
confidence: 99%
“…The external flow of vapour creates interfacial shear which may enhance the condensation heat transfer coefficient, depending on the direction of flow of vapour. Some important investigations on the external flow of vapour over the condenser tube have been made by several researchers (Shekariladge and Gomeluri, 1966;Fujji et al, 1979;Lee et al, 1984;Memory et al, 1993;and Michael et al, 1989). These investigators were primarily concerned with the estimation of condensation heat transfer coefficients under isothermal conditions of the tube wall.…”
Section: Introductionmentioning
confidence: 99%
“…(2.27) (jr and '77«/ Equation 2.26 satisfies the limiting cases for both large and small vapor velocities and was found by Lee and Rose (1984) to give reasonable results to existing data. At values of G greater than 5 (infinite condensation rate), Equation 2.26 almost duplicates the solutions found using Equation 2.24.…”
mentioning
confidence: 57%
“…Both Honda et al (1982) and Lee and Rose (1984) found that these theories tended to overpredict the experimental Nu values for steam at relatively high vapor velocities and underpredict them for CFC-113 data taken at moderate velocities. Noting these discrepencies.…”
Section: _1mentioning
confidence: 98%
See 1 more Smart Citation